Generalized Mixed Equilibrium Problems for Maximal Monotone Operators and Two Relatively Quasi-Nonexpansive Mappings: Kriengsak Wattanawitoon, Poom Kumam - Team, Support (Thai Journal of Mathematics, 2011)
In this paper, we prove the strong convergence theorems of modified hybrid projection methods for finding a common element of the set of solutions of generalized mixed equilibrium problems, the set of solution of the variational inequality operators of an inverse strongly monotone, the zero point of a maximal monotone operator and the set of fixed point of two relatively quasi-nonexpansive mappings in a Banach space. Our results modify and improve the recently ones announced by many authors.